Caseload of general surgeons working in a rural hospital with outreach practice. Issue 7 (30th August 2012) - Campbell, Nicole A.; Franzi, Stephen; Thomas, Peter
Abstract Background There is little published data regarding the caseloads of general surgeons working in rural Australia conducting outreach services as part of their practice. It remains difficult to attract and retain surgeons in rural Australia. This study aims to describe the workload of surgeons working in a rural centre with outreach practices in order to determine the required skills mix for prospective surgeons. Methods A retrospective review of surgical procedures carried out by two surgeons over 5 years working from a base in Wangaratta, Victoria, with outreach services to Benalla, Bright and Mansfield was undertaken. Data were extracted from surgeon records using Medicare Benefits Schedule item numbers. Results A total of 18 029 procedures were performed over 5 years, with 15% of these performed in peripheral hospitals as part of an outreach service. A full range of general surgical procedures were undertaken, with endoscopies accounting for 32% of procedures. In addition, vascular procedures and emergency craniotomies were also performed. The majority of procedures undertaken at peripheral centres were minor procedures, with only two laparotomies performed at these centres over 5 years. Conclusion General surgeons working in rural centres are required to have broad skills and be able to undertake a large number of procedures. Trainees should be encouraged to consider rural practice, and those who are interested should consider the needs of the community in which they intend to practice. Outreach work to surrounding communities can be rewarding for both the surgeon and the community.